MOTIVASI BERKUNJUNG DAN PERSEPSI WISATAWAN NUSANTARA TERHADAP KUALITAS PELAYANAN DI TOYA DEVASYA DESA BATUR KINTAMANI - Wiramatika, I Gede; Eka Mahadewi, Ni Putu; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 1 (2018): Jurnal IPTA (July 2018)DO - 10.24843/IPTA.2018.v06.i01.p05, 2018)
This research observed the Toya Devasya, Kintamani. The aim of this research are 1) to know the motivation of domestic tourist’s that visit the Toya Devasya Kintamani, Bangli. 2) to know their perception in regards of its service quality. This research used sample determination method which tend to purposive with taking its sample by using accidental sampling method and determining the number of samples using quota sampling giving 100 questioners to domestic tourist. Data collection technique that used is by interview, observing, documentation, literature study and questioner with analysis technique by qualitative and quantitative descriptive. The result showed the motivation which push domestic tourist’s to visit Toya Devasya are to make the mind calm, relax and free yourself in a beautiful and interesting place, get a new atmosphere. At the same time the motivation that pull those tourist’s to visit Toya Devasya is the beauty of natural mountain kicking, a nice atmosphere to be enjoyed, the source of hot water coming from Mount Batur. The perception of domestic tourist’s to its service quality over all is good, however they still feel that the lack of assurance service in Toya Devasya.